Juristic Differences on Salat Within the Maliki School and Its Relevance to Nigerian Muslims - AbdulWahhab Danladi Shittu; AbdulWaheed Olarewaju Yakub (Al-Arfa: Journal of Sharia, Islamic Economics and Law, 2024)
Salat, or Islamic prayers, is central to Muslim devotion globally. However, different schools of Islamic jurisprudence interpret and apply Salat uniquely. The Maliki school stands out for its distinct approach, influencing how Salat is performed. In Nigeria, where Maliki jurisprudence predominates among Muslims, these differences are especially relevant. Nigeria's diverse Muslim population offers an ideal setting to explore how Maliki jurisprudence impacts Salat practice and religious identity. This study examines the unique interpretations and rulings of the Maliki school regarding Salat, focusing on prayer methodology such as mode of Iqᾱmah, Adhᾱn, recitations, Al-Qunũt, Qabd and Sadl, and evaluates their relevance to Nigerian Muslims. The research employs textual analysis and comparative jurisprudence to uncover doctrinal differences and practical implications of Maliki rulings on Salat. Empirical data from Nigerian Muslim communities shed light on how these differences affect contemporary Salat practices and perceptions. Findings revealed that Maliki jurisprudence remains influential among Nigerian Muslims, providing a foundational framework for religious guidance. Despite divergence, the core principles of Shari’ah and its sources remain intact. Conclusively, the paper emphasisesthe importance of fostering dialogue and understanding among scholars, policymakers, and religious leaders to enhance spiritual experiences and communal cohesion in Nigerian Muslim society.